2014
DOI: 10.1002/ange.201408845
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Platinum Species in Polymer Electrolyte Fuel Cells by Spatially Resolved XAFS Techniques

Abstract: There is limited information on the mechanism for platinum oxidation and dissolution in Pt/C cathode catalyst layers of polymer electrolyte fuel cells (PEFCs) under the operating conditions though these issues should be uncovered for the development of next-generation PEFCs. Pt species in Pt/C cathode catalyst layers are mapped by a XAFS (X-ray absorption fine structure) method and by a quick-XAFS-(QXAFS) method. Information on the site-preferential oxidation and leaching of Pt cathode nanoparticles around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… 75 The ability to detect variations in the concentrations of the absorbing species is also critical for studies of heterogeneous samples, and is especially useful when combined with the possibility to scan the position of the X-ray beam. A good illustration of this is the study by Takao et al, 104 where the spatial distribution of Pt species at the cathode of polymer electrolyte fuel cells was mapped, Figure 4 a. The proportionality of the XAS signal to the number of absorbing species is also a useful tool to verify the relative concentrations of different metals in multielement systems such as bimetallic nanocatalysts.…”
Section: From Descriptors To Physical Models Of Electrocatalyst Strucmentioning
confidence: 93%
See 2 more Smart Citations
“… 75 The ability to detect variations in the concentrations of the absorbing species is also critical for studies of heterogeneous samples, and is especially useful when combined with the possibility to scan the position of the X-ray beam. A good illustration of this is the study by Takao et al, 104 where the spatial distribution of Pt species at the cathode of polymer electrolyte fuel cells was mapped, Figure 4 a. The proportionality of the XAS signal to the number of absorbing species is also a useful tool to verify the relative concentrations of different metals in multielement systems such as bimetallic nanocatalysts.…”
Section: From Descriptors To Physical Models Of Electrocatalyst Strucmentioning
confidence: 93%
“…For example, Takao et al recently demonstrated the possibility to use QXAFS and a scanning X-ray beam to map the distribution of different Pt species at the cathode of polymer electrolyte fuel cells, where the increased Pt oxidation state was associated with the degradation of the catalyst and correlated in space with the presence of microcracks in the cathode layer ( Figure 4 ). 104 Without doubt, the importance of spatially- and time-resolved XAS studies for the understanding of catalyst under working conditions will further increase in the future. However, one of the challenges to be addressed in these experiments includes the very large data sets produced, which requires some further development in automatic data processing and analysis.…”
Section: Xas Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work by Garcia-Sanchez et al has used current mapping to show the localised degradation of PEFCs, with SEM used for ex-situ visualisation of platinum in the membrane [29]. Such non-uniform degradation has been reported by a number of practitioners, but, until now, only in 2D, ex-situ SEM studies [11,[28][29][30] or by using nano-scale techniques, like X-ray absorption fine structure (XAFS) or scanning transmission electron microscopy-energy dispersive X-ray spectroscopy (STEM-EDS) [31]. However, 3D imaging of the microstructural degradation effects that accompany localised electrochemical degradation have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Although SEM imaging offers high resolution, it only provides external information from the exposed surface in a 2D image. TEM and related methods, such as scanning TEM (STEM), offer even higher resolution and can be extended to 3D tomography. STEM imaging in conjunction with energy-dispersive X-ray spectroscopy (EDS or EDX) had been used for chemical mapping of the materials. , However, the transmission imaging requires the sample to be very thin, on the order of 100 nm. ,,, X-ray-computed laminography (XCL) has also been combined with X-ray absorption fine structure (XAFS) to analyze the chemical states of Pt in the fresh and cycled catalyst layer along with 3D morphological characterization . Focused ion beam (FIB) milling combined with SEM can provide high-resolution 3D morphology of the catalyst layer. , However, FIB-SEM faces its own set of challenges.…”
Section: Introductionmentioning
confidence: 99%